The immunological synapse: the gateway to the HIV reservoir. Issue 1 (16th June 2013) - Kulpa, Deanna A.; Brehm, Jessica H.; Fromentin, Rémi; Cooper, Anthony; Cooper, Colleen; Ahlers, Jeffrey; Chomont, Nicolas; Sékaly, Rafick‐Pierre
Summary: A major challenge in the development of a cure for human immunodeficiency virus (HIV) has been the incomplete understanding of the basic mechanisms underlying HIV persistence during antiretroviral therapy. It is now realized that the establishment of a latently infected reservoir refractory to immune system recognition has thus far hindered eradication efforts. Recent investigation into the innate immune response has shed light on signaling pathways downstream of the immunological synapse critical for T‐cell activation and establishment of T‐cell memory. This has led to the understanding that the cell‐to‐cell contacts observed in an immunological synapse that involve the CD4 + T cell and antigen‐presenting cell or T‐cell–T‐cell interactions enhance efficient viral spread and facilitate the induction and maintenance of latency in HIV‐infected memory T cells. This review focuses on recent work characterizing the immunological synapse and the signaling pathways involved in T‐cell activation and gene regulation in the context of HIV persistence.